Diabetes and intracerebral hemorrhage: baseline characteristics and mortality. (26th March 2018) - Liebkind, R.; Gordin, D.; Strbian, D.; Meretoja, A.; Thorn, L. M.; Hägg‐Holmberg, S.; Forsblom, C.; Tatlisumak, T.; Groop, P.‐H.; Putaala, J.
Abstract : Background and purpose: Acknowledging the conflicting evidence for diabetes as a predictor of short‐ and long‐term mortality following an intracerebral hemorrhage (ICH), we compared baseline characteristics and 30‐day and long‐term mortality between patients with and without diabetes after an ICH, paying special attention to differences between type 1 (T1D) and type 2 (T2D) diabetes. Methods: Patients with a first‐ever ICH were followed for a median of 2.3 years. Adjusting for demographics, comorbidities and documented ICH characteristics increasing mortality after ICH, logistic regression analysis assessed factors associated with case fatality and 1‐year survival among the 30‐day survivors. Diabetes was compared with patients without diabetes in separate models as (i) any diabetes and (ii) T1D or T2D. Results: Of our 969 patients, 813 (83.9%) had no diabetes, 41 (4.2%) had T1D and 115 (11.9%) had T2D. Compared with patients without diabetes, those with diabetes were younger, more often men and more frequently had hypertension, coronary heart disease and chronic kidney disease, with similar ICH characteristics. Patients with T1D were younger, more often had chronic kidney disease and brainstem ICH, and less often had atrial fibrillation and lobar ICH, than did patients with T2D. Diabetes had no impact on case fatality. Any diabetes (odds ratio, 2.57; 1.19–5.52), T1D (odds ratio, 7.04; 1.14–43.48) and T2D (odds ratio, 2.32; 1.04–5.17) were independently associated with 1‐year mortality. Conclusions: Patients with ICH with diabetes exhibited a distinct pattern of comorbidities and disease characteristics with specific differences between T1D and T2D. Despite their younger age, T1D seems to carry a substantially higher likelihood of long‐term mortality after an ICH than does T2D.